Potential of market discipline in Pakistan: The bank depositors’ perspective - Mirza, Nawazish; Naqvi, Bushra; Rizvi, Syed Kumail Abbas; Rahat, Birjees (International Food Policy Research Institute, 2016)
The aim of this research is to ascertain whether Pakistan’s financial system is conducive to market disci-pline. We measure the potential of depositors to induce market discipline in the commercial banking sector. A comprehensive survey of over six thousand respondents was used to gauge their propensity to discipline bank management in response to deteriorating financial conditions. Our results portray that depositors are likely to withdraw funds in response to a reduction in profitability, an increase in non-performing loans, and a reduction in total assets. We identify that banks with better service quality are less sensitive to deposit withdrawals in the event of a reduction in their financial performance. Among other findings, the presence of contractual guarantees by the government desensitizes depositors to market information, making them less likely to be involved in imposing market discipline.